Edukacja przyrodnicza w klasach początkowych w koncepcjach studentów pedagogiki wczesnej edukacji. W ślepej uliczce faktografii - Alicja Komorowska-Zielony (Problemy Wczesnej Edukacji)
The article presents students’ concepts of early science education, especially assumptions, possibilities and examples of this kind of teaching-learning. There is also an attempt to determine the status of early science education. The main idea of the text is a child as an explorer, especially at the first level of primary school.